Large pelvic mass - careful planning - can decrease the morbidity - Kankanala, Jyoti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
We report a case of a 43-year old woman with a 24-26 weeks size pelvic mass, inspite of CT contrast pelvis the exact location of mass remained unclear. At laparotomy, it was found to be a broad ligament multilobulated leiomyoma measuring 20-24cm and weighing, approximately 1400gms. We are reporting this to emphasize the importance of planning a case and involving different team members in case of large mass with an anticipation of complications and also a pathologist a day prior about the need for frozen section.